EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH TERHADAP KEJENUHAN SISWA - Hery Kristanto, Vigih (Widya Warta, 2016)
This study is an attempt to find out whether saturation of students in Problem Based Learning is lower than saturation of students in direct teaching. Saturation in question is students’ degree of saturation obtained from the scores of questionnaires on saturation which were already completed by students. It is a quasi-experimental quantitative research. The data of Pythagoras Theorem material were taken from the eight-year-students of SMP Negeri 4 Madiun of the even semester of the academic year 2013/2014 and those of opportunities material were obtained from the nine-year-students of SMP Negeri 3 Madiun of the odd semester of the academic year 2014/2015. The population used as a medium of generalization is all the students of SMP Negeri located in Madiun. The data collecting made use of questionnaires on students’ saturation. The statistical analysis employed is a non-parametric statistical test, namely the Mann Whitney test. The results indicated that the saturation of students who joined the Problem Based Learning process is lower than the saturation of students who joined the direct teaching process.